Development of Digital Learning Media Based on Google Sites to Improve Student Learning Outcomes - Melda Sari; Ramalis Hakim; Darmansyah; Jasrial (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to develop and evaluate a Google Sites-based learning medium for teaching Visual Arts to Grade X high school students. The research employed a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation phases. Data were collected through observation, interviews, questionnaires, and documentation. The developed media was assessed by subject matter, media, and language experts and determined to be highly valid. Practicality testing with teachers and students indicated that the media was very practical for classroom use. Effectiveness was evaluated using pre-test and post-test comparisons, showing a moderate improvement in students' cognitive learning outcomes, based on an N-Gain score in the medium category. These findings suggest that the Google Sites-based media is a valid, practical, and potentially effective tool for enhancing student engagement and understanding in Visual Arts education.